2017
DOI: 10.1038/s41598-017-12026-x
|View full text |Cite|
|
Sign up to set email alerts
|

Development of chloroplast genome resources for peanut (Arachis hypogaea L.) and other species of Arachis

Abstract: AbsractPeanut (Arachis hypogaea L.) is an important oilseed and cash crop worldwide. Wild Arachis spp. are potental sources of novel genes for the genetic improvement of cultivated peanut. Understanding the genetic relationships with cultivated peanut is important for the efficient use of wild species in breeding programmes. However, for this genus, only a few genetic resources have been explored so far. In this study, new chloroplast genomic resources have been developed for the genus Arachis based on whole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 63 publications
9
25
1
Order By: Relevance
“…2). These results showed that the SSRs exhibit a strong AT bias, which is consistent with the observed in other Leguminosae species, such as Vigna radiata 55 , Cajanus cajan 10 , Cajanus scarabaeoides 10 and Arachis hypogaea 56 .
Figure 2Number and type of simple sequence repeats in S. adstringens chloroplast genome.
…”
Section: Resultssupporting
confidence: 87%
“…2). These results showed that the SSRs exhibit a strong AT bias, which is consistent with the observed in other Leguminosae species, such as Vigna radiata 55 , Cajanus cajan 10 , Cajanus scarabaeoides 10 and Arachis hypogaea 56 .
Figure 2Number and type of simple sequence repeats in S. adstringens chloroplast genome.
…”
Section: Resultssupporting
confidence: 87%
“…Structural mutations are potential informative phylogenetic characters of low homoplasy if handled properly. For example, Arachis [53], yam [54], and Cynara [55] have 85, 43, 34 indels in their whole chloroplast genomes, respectively. However, the direction of structural mutations are of less focus [56].…”
Section: Direction Of Mutationsmentioning
confidence: 99%
“…The genomes of the diploid progenitor species of cultivated peanut have been sequenced (Bertioli et al 2016;Chen et al 2016b). Recently, the chloroplast genomes of seven species have also been sequenced (Yin et al 2017) to understand the genetic relationships of the wild species with the cultivated peanut. A molecular phylogeny based on the complete chloroplast genome sequences provided the best resolution of the seven Arachis species.…”
Section: Introductionmentioning
confidence: 99%